Biomechanical Evaluation of Different Implant-Abutment Connections,Retention Systems,and Restorative Materials in the Implant-Supported Single Crowns Using 3D Finite Element Analysis - Lemos, Cleidiel Aparecido Araujo; Verri, Fellippo Ramos [UNESP]; Noritomi, Pedro Yoshito; de Souza Batista, Victor Eduardo; Cruz, Ronaldo Silva [UNESP]; de Luna Gomes, Jessica Marcela [UNESP]; de Oliveira Limírio, João Pedro Justino [UNESP]; Pellizzer, Eduardo Piza [UNESP] (American Academy of Implant Dentistry, 2022)
This is an in silico study aimed to evaluate the biomechanical influence of different implant-abutment interfaces (external hexagon and Morse taper implants), retention systems (cement and screw retained), and restorative crowns (metal-ceramic and monolithic) using 3-dimensional finite element analysis (3D-FEA). Eight 3D models were simulated for the maxillary first molar area using InVesalius, Rhinoceros, and SolidWorks and processed using Femap and NEi Nastran software. Axial and oblique forces of 200 and 100 N, respectively, were applied on the occlusal surface of the prostheses. Microstrain and von Mises stress maps were used to evaluate the deformation (cortical bone tissue) and stress (implants/fixation screws/crowns), respectively, for each model. For both loadings, Morse taper implants had lower microstrain values than the external hexagon implants. The retention system did not affect microstrain on the cortical bone tissue under both loadings. However, the cemented prosthesis displayed higher stress with the fixation screw than the external hexagon implants. No difference was observed between the metal-ceramic and zirconia monolithic crowns in terms of microstrain and stress distribution on the cortical bone, implants, or components. Morse taper implants can be considered as a good alternative for dental implant rehabilitation because they demonstrated better biomechanical behavior for the bone and fixation screw as compared to external hexagon implants. Cement-retained prosthesis increased the stress on the fixation screw of the external hexagon implants, thereby increasing the risk of screw loosening/fracture in the posterior maxillary area. The use of metal-ceramic or monolithic crowns did not affect the biomechanical behavior of the evaluated structures.
Keywords: connection system; dental implant; metal free; retention system